Recent Progress on the Implementation of Renewable Biodiesel Fuel for Automotive and Power Plants: Raw Materials Perspective - Jayan Sentanuhady; Wisnu Hozaifa Hasan; Muhammad Akhsin Muflikhun (Advances in Materials Science and Engineering)
The issue of energy availability and the impact of global warming has become a specific concern for researchers in various countries in the world. This condition opens up space for potential alternative energy sources that are newer and more sustainable. Biodiesel as a sustainable alternative energy can be applied directly to industrial and automotive fields and even as a fuel source for power plants. This study provides a specific overview of the use and development of biodiesel as a fuel source for renewable power generation based on material sources. An essential part of this study discusses the development of various combinations of biodiesel mixtures and their applications in various types of industries. The physical and chemical characteristics of various types of biodiesel have been studied for their use in various parts of the world. The use of biodiesel has a positive effect on reducing emissions and pollutants, but a particular method is needed to optimize the efficiency and effectiveness, both technically and nontechnically. However, the utilization accompanied by optimizing the characteristics and parameters of biodiesel shows that this alternative energy is feasible and can be applied as a renewable fuel source for automotive industry and power generation in the future.